From The Lack of Women Representation to the Case of Comfort Women: An Analysis of Gender Issues in Diplomacy and Diplomatic Relations - Azzahra, Syifa Kamila; Latifah, Emmy (Journal of ASEAN Dynamics and Beyond, 2021)
As time goes by, public awareness of gender issues is reaching an uphill trend, due to the increasing number of activism movements concerning it. The scope of diplomacy is not an aspect that is free from the problem of gender inequality. Starting with analyzing the under-representation of women in diplomatic posts issue, to the case of comfort women that characterizes diplomatic relations between South Korea and Japan, this article aims to provide an illustration that shows the fact of even though there has been better inclusiveness, there is still nevertheless a need for reforms in the world diplomacy system to be more open to the principals of gender equality.